Case Study : Elrah Exclusive / Nur Iffah Malihah Rozi - Rozi, Nur Iffah Malihah (2021)
The case study is important to evaluate the company’s background, company’s analysis as well as the company’s problems all alternatives that the management has provided. The methods that used to study the analysis is face-to-face interviews with the management of the company through phone call and review from people already have purchased and taste the products. But here, my case study is individual because we are in PKP. So, I already chose the products in google. This is an attempt to find out how the theory can be applied to practical situations. As a student at UiTM Kelantan Machang Campus, it was part of the study for me to undertake a case study project. So, for this purpose, I had the opportunity to research a company that produces clothing products, named Elrah Exclusive, which is currently located at KBMall Kota Bharu Kelantan. For the project report, the first step is the general information of the company has been gathered and the information is gathered through the primary and secondary sources for example we interviewed the owner of Elrah Exclusive and we also gathered information about Elrah Exclusive through the Instagram and Facebook Platforms. The second part is, specialized subject study which the objective of the project is to view background, organizational structure, products and services that have been provided in Elrah Exclusive. Next, we study about men's clothing and accessories industry. After that, I learned about the technology or system that have been used in Elrah Exclusive and marketing strategy used by the company to promote their product is really interesting. Lastly, market and place. In this case study, we also analyzed the strength, weaknesses, opportunities and threats of this company in real business world by using SWOT analysis.